Las Intervenciones Intergrupales como estrategia de STRATCOM - Díaz Robredo, Luis Ángel (Journal of the Spanish Institute for Strategic Studies, 2026)
Strategic communication is one of the tools that has seen the greatest progress in recent years within NATO. Its capabilities to act on the cognitive sphere make it highly effective in reinforcing the influence of military power between civilians and the military. The interest in information warfare that has emerged since the invasion of Crimea has motivated the development of strategic communication capabilities. By reviewing some theories of social and group psychology, we will review a series of intergroup interventions that have proven effective in reducing prejudice and animosity between groups, thus advancing conflict management and strengthening the capabilities of all elements involved in NATO's action, in line with the narratives to be conveyed.
Keywords: Narratives; Cognitive; Group Psychology; Prejudice; Information warfare